PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN PENDIDIKAN PANCASILA UNTUK MEMBENTUK KARAKTER SISWA SEKOLAH DASAR: STUDI LITERATUR - Mutia Afiska; Usnahtul Asnah; Melisa Indriani; Ari Suriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pancasila Education plays a strategic role in shaping the character of elementary school Pancasila Education plays a strategic role in shaping the character of elementary school students as the next generation with a Pancasila spirit. However, learning Pancasila Education in elementary schools is often still abstract, verbalistic, and less meaningful for students. The contextual approach (CTL) serves as a solution by connecting learning materials with students' real lives. This article aims to examine the application of the contextual approach in Pancasila Education learning to shape students' character through a systematic literature study of eight related journals. Literature search was conducted through Google Scholar and Sinta databases using the keywords contextual approach, CTL, Pancasila Education, and elementary student character, with inclusion criteria of publications from 2021–2024. Results show that CTL, implemented through its seven main components, significantly improves students' understanding and internalization of Pancasila values, including religiosity, honesty, mutual cooperation, responsibility, and nationalism. Although all reviewed literature demonstrates positive outcomes, the main challenge lies in shifting paradigms and teachers' readiness to consistently implement CTL.